Um olhar Bakhtiniano sobre ensino de língua portuguesa para surdos - Teichmann, Andreza Mariane Batista (2016)
This research analyzes the two volumes of books offered by the Ministry of Education as the guiding material from Portuguese-speaking school for deaf students in Brazil. It uses the discursive dialogical point of view established by Bakhtin's theory. The overall objective of the study was to determine, based on sentences obtained from the books, how the deaf students understand the Portuguese language teacher work. With this objective, the constructions of sentences were observed and the possible identification of the subject-interlocutor, namely the auditorium designed by these discourses. As for the dialogical construction of the senses, we tried to observe what effects intended by the enunciation projects and readings performed by the alleged interlocutors reached such understanding. As for the specific objectives we intend to (a) identify the language concepts underlying the books that guide the Portuguese education for deaf students in Brazil aiming to establish a relation to Bakhtin’s discursive theory that contribute to teaching; (b) detect, also through the sentences, a possible understanding of other subjects involved in this discourse, i. e., how the Portuguese language teacher is understood by the deaf students and the students themselves; and (c) identify a way that the Bakhtinian postulates can add new contributions to the Portuguese-speaking school for deaf students in Brazil. With this objective, some of the sentences contained in the books were portrayed during the analysis. The developed research was based on the understanding of language/ language currently in use, such as the Bakhtin Circle understands it, using the discursive gender concepts, statements, active responsiveness, sense and dialogism. The constant interactions with the ideas set by the Circle enabled the reflections about the different meanings that the sentences made in the instructional materials for the Portuguese language teaching to deaf students. Deepening into the Circle’s studies also provided a better understanding of how the meaning given to each element can build different senses, leaving only the constituent components of linguistic discourse. Considering this, identifying the voices that are engendered in discourse and contrast them with the authors’ enunciation project, with the proposal established by the books, favored the understanding of Bakhtin's proposal for a responsive attitude of the reader considering the displayed discourse. Such understanding allowed the conclusion about the ideological confrontation that was established, since the distinct valuation, awarded by each party to the discourse, is the reason that generates this confrontation.